Photoactive semiconducting metal oxides: Hydrogen gas sensing mechanisms. (12th May 2022) - Thathsara, S.K.T.; Harrison, C.J.; Hocking, R.K.; Shafiei, M.
Abstract: The use of photactive nano materials in gas sensors is a promising and novel strategy to enhance key sensing properities including sensitivity, selectivity, durability and improved manufacture costs and power consumption. Photoactive gas sensors can also be used as an alternative to thermal heating gas sensing processes. This review article provides an overview of hydrogen gas sensing mechanisms exhibited by different semiconducting metal oxides (SMOx) and their derivatives under Ultra-Violet (UV) and visible light conditions while examining tunable gas sensing properties and unique morphological properties. Most of the materials discussed have been newly developed and show promise for hydrogen gas sensing under photoactive conditions at room temperature. In addition, we explore the dependence of the sensing properties on the width of electron depletion layer, the effect of heterojunction as well as the effect of modifications of the sensing material/s (including varying the photoactive SMOx materials, SMOx functionalized with noble metals (as dopants), graphene-based materials and natural derivatives). Finally, advantages and limitations of the sensing properties are summarized to enhance further development of SMOx materials and their derivatives towards hydrogen gas sensing.